Corporate Rebranding and Performance of Financial Institutions in Ghana - Yeboah, Pearl Owusua; Addaney, Michael (Journal of Asian Business Strategy, 2016)
Rebranding has become a popular topic to organizations, banks especially, in the past few years. The study sought to ascertain the impact of corporate rebranding on an organization’s image and performance. Factors that cause rebranding and the measures that organizations put in place to promote positive image and enhance performance after rebranding were also examined. Through convenient sampling technique, 114 respondents comprising of customers and employees from the Agricultural Development Bank, Sunyani branch were interviewed. The study revealed that, respondents (customers and employees) saw competition as the major cause of the bank’s identity change. They however had opposing views on the effect of the new identity of the bank on its image and performance. The employees observed that the bank’s performance had improved through new measures such as training and development, provision of logistics and deployment of new technologies, customers were unsatisfied with the branch’s performance because they felt that certain issues such as malfunctioning of the ATM, insufficient number of tellers, long transaction time and congestion in the banking hall had been ignored by the bank. Among other things, the study recommends that the bank increases resources to ensure better and quality service provision.